The protective effects of active ingredients from acrorus tatarinowii on sperm and their molecular mechanisms - Zonglin Lu; Haiyang Zhao; Hui Wang; Xin Wang; Zixue Sun (Basic and Clinical Andrology)
Abstract Purpose To investigate the therapeutic potential of Acrorus tatarinowii in oligoasthenozoospermia and its related mechanism through modulation of the BCL2/Bax/Caspase3 signaling pathway. Methods Initially, using the TCMSP and Disgenet databases, active ingredients of Acrorus tatarinowii were identified and their target genes associated with sperm-related diseases were elucidated.Subsequently, an oligoasthenozoospermia mouse model was induced and treated with Acrorus tatarinowii. Serum hormone levels were assessed by ELISA, testicular histopathology by HE staining, and target gene expression by qPCR and Western blotting. Results Acrorus tatarinowii treatment significantly upregulated BCL2 expression in the testes of oligoasthenozoospermic rat. This was accompanied by improved histopathological features in testicular tissues, reduced LH and FSH levels in serum. Conclusion Acrorus tatarinowii exerts therapeutic effects in oligoasthenozoospermia by regulating the BCL2/Bax/Caspase3 pathway, maybe by inhibiting apoptosis, and promoting germ cell proliferation. These findings highlight its potential as a natural remedy for male infertility associated with sperm function disorders.